The effects of endurance, strength, and power training on muscle fiber type shifting - Wilson, J. M.; Loenneke, J. P.; Jo, E.; Wlson, G. J.; Zourdos, M. C.; Kim, J. -S. (The Journal of Strength and Conditioning Research, 2012)
Muscle fibers are generally fractionated into type I, IIA, and IIX fibers. Type I fibers specialize in long duration contractile activities and are found in abundance in elite endurance athletes. Conversely type IIA and IIX fibers facilitate short-duration anaerobic activities and are proportionally higher in elite strength and power athletes. A central area of interest concerns the capacity of training to increase or decrease fiber types to enhance high-performance activities. Although interconversions between type IIA and IIX are well recognized in the literature, there are conflicting studies regarding the capacity of type I and II fibers to interconvert. Therefore, the purpose of this article is to analyze the effects of various forms of exercise on type I and type II interconversions. Possible variables that may increase type II fibers and decrease type I fibers are discussed, and these include high velocity isokinetic contractions; ballistic movements such as bench press throws and sprints. Conversely, a shift from type II to type I fibers may occur under longer duration, higher volume endurance type events. Special care is taken to provide practical applications for both the scientist and the athlete.